Resolvin E1 Inhibits Substance P-Induced Potentiation of TRPV1 in Primary Sensory Neurons - Youn Yi Jo; Ji Yeon Lee; Chul-Kyu Park (Hindawi Limited, 2016)
The neuropeptide substance P (SP) is expressed in primary sensory neurons and is commonly regarded as a "pain" neurotransmitter. Upon peripheral inflammation, SP activates the neurokinin-1 (NK-1) receptor and potentiates activity of transient receptor potential vanilloid subtype 1 (TRPV1), which is coexpressed by nociceptive neurons. Therefore, SP functions as an important neurotransmitter involved in the hypersensitization of inflammatory pain. Resolvin E1 (RvE1), derived from omega-3 polyunsaturated fatty acids, inhibits TRPV1 activity via activation of the chemerin 23 receptor (ChemR23)-an RvE1 receptor located in dorsal root ganglion neurons-and therefore exerts an inhibitory effect on inflammatory pain. We demonstrate here that RvE1 regulates the SP-induced potentiation of TRPV1 via G-protein coupled receptor (GPCR) on peripheral nociceptive neurons. SP-induced potentiation of TRPV1 inhibited by RvE1 was blocked by the Gαi-coupled GPCR inhibitor pertussis toxin and the G-protein inhibitor GDPβ-S. These results indicate that a low concentration of RvE1 strongly inhibits the potentiation of TRPV1, induced by the SP-mediated activation of NK-1, via a GPCR signaling pathway activated by ChemR23 in nociceptive neurons. RvE1 might represent a new therapeutic target for the treatment of inflammatory pain as a prospective endogenous inhibitor that strongly inhibits TRPV1 activity associated with peripheral inflammation.